Modelling of a straw tracker in the NA64 experiment on the M2 SPS muon beam in the GEANT4 software environment - Turganova, S.A.; Saduyev, N.O.; Myktybekov, D.Y.; Enik, T.L.; Mukhamejanov, Y.S.; Pshikov, M.I. (Recent Contributions to Physics, 2022)
The NA64 experiment is aimed at searching for mediator particles that carry out the interaction between standard matter and dark matter. The main goal of the experiment is to detect Light Dark Matter (LDM) particles with masses below 1 GeV. The missing energy/momentum technique is used in the experiment, e.g. in the muon run energy of muons in the final state is expected to be 80 GeV. The NA64 experiment has a fairly extensive detector system, including several types of detectors. Straw trackers are used in both muon and electron modes of the experiment. One of the essential components of the detection system along the beamline is the straw tube detector. Straw trackers allow one to reconstruct the tracks of primary and secondary particles and subsequently estimate their momentum based on the curvature of the track. This paper presents a straw tracker model built using the Geant4 software package. Secondary radiation particles were also included in straw tube responses. The main goal of this work is to construct and analyze a straw tracker model using the GEANT4 toolkit. The research methodology is based on the use of the Monte Carlo method, which underlies the work of GEANT4. The results of the study have practical significance, consisting in the use of models for optimizing the technical and design parameters of straw trackers.